2008
DOI: 10.1175/2008mwr2378.1
|View full text |Cite
|
Sign up to set email alerts
|

Vortex Interactions and Barotropic Aspects of Concentric Eyewall Formation

Abstract: Concentric eyewall formation can be idealized as the interaction of a tropical cyclone core with nearby weaker vorticity of various spatial scales. This paper considers barotropic aspects of concentric eyewall formation from modified Rankine vortices. In this framework, the following parameters are found to be important in concentric eyewall formation: vorticity strength ratio, separation distance, companion vortex size, and core vortex skirt parameter. A vorticity skirt on the core vortex affects the filament… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
91
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(92 citation statements)
references
References 48 publications
1
91
0
Order By: Relevance
“…The maximum 1-min sustained wind speed was derived using the Dvorak T number. The microwave data are used to define the CE structure, the inner eyewall radius, Kallenbach 1997) and axisymmetrization of binary vortex interaction (Kuo et al 2004(Kuo et al , 2008. These dynamics highlight the importance of the strong core vortex.…”
Section: Data Methods and Climatologymentioning
confidence: 99%
See 2 more Smart Citations
“…The maximum 1-min sustained wind speed was derived using the Dvorak T number. The microwave data are used to define the CE structure, the inner eyewall radius, Kallenbach 1997) and axisymmetrization of binary vortex interaction (Kuo et al 2004(Kuo et al , 2008. These dynamics highlight the importance of the strong core vortex.…”
Section: Data Methods and Climatologymentioning
confidence: 99%
“…Compared to the non-concentric eyewall typhoon composite, the concentric composite shows a relatively high intensity for a longer duration, rather than a rapid intensification process that can reach a higher intensity. Kuo et al (2004Kuo et al ( , 2008 hypothesized that axisymmetrization of positive vorticity perturbations around a strong and tight core of vorticity may lead to the formation of concentric eyewalls. The long duration of high intensity before secondary eyewall formation may provide a favorable environment for the axisymmetrization dynamics to operate.…”
Section: Intensity Changementioning
confidence: 99%
See 1 more Smart Citation
“…Kuo et al (2004) suggests the pivotal role of the vorticity strength of the core vortex in maintaining itself, and in strectching, organizing and stabilizing the outer vorticity field, and the shielding effect of the moat to prevent further merger and enstrophy cascade processes in concentric eyewall dynamics. Kuo et al (2008) further suggests that double eyewall of different sizes maybe explained by the binary vortex interaction with skirted parameter. The result also suggests that vorticity generation in the core and in the environment (via mesoscale convection) are of great importance in double eyewall dynamics.…”
Section: Concentric Eyewall Cyclesmentioning
confidence: 88%
“…The radar observation of typhoon Lekima (2001) near Taiwan (Kuo et al, 2004) indicates a huge area of convection outside the core vortex wraps around the inner eyewall to form concentric eyewalls in about 12 hours. Kuo et al (2008) also reported cases of passive microwave data that the formation of a concentric eyewall from organization of asymmetric convection outside the primary eyewall into a symmetric band that encircled the eyewalls. Two such concentric eyewalls examples are shown in Fig.…”
Section: Concentric Eyewall Cyclesmentioning
confidence: 96%